THERAPEUTIC APPLICATIONS IN NEOPLASMS AT THE ESOPHAGOGASTRIC JUNCTION (CIPEEX, 2025)
Introduction: Gastric cancer is the third most prevalent cancer worldwide, with increasing rates over the years, while esophageal carcinoma ranks sixth in global recurrence. Among studies, there is no consensus on whether cancer at the esophagogastric junction is associated with the gastric or esophageal space. However, it is considered one of the most aggressive types of cancer. Surgical therapy remains the primary curative approach, though complications such as anastomotic fistula are common. Neoadjuvant chemotherapy and nutritional therapies are being evaluated to enhance treatment and remission rates.Methodology: This integrative review analyzed 24 articles from Scielo, Medline, and Lilacs databases, narrowing down to 5 relevant studies. Articles were in English and Portuguese, original, and published within the last 10 years. The guiding question was: "What therapeutic approaches are applicable to patients with cancer at the esophagogastric junction?"Objective: To analyze the types of therapeutic actions, effects, and outcomes in cases of esophagogastric junction neoplasms.Results:Neoadjuvant chemotherapy increases cure chances by 10% and improves prognosis when combined with surgery.Gastrectomies have a morbidity rate of 33.5% and a mortality rate of 0.6%-4.7%.Esophagectomy has postoperative mortality of up to 24%.Immunonutrition enhances recovery and reduces complications.Surgical intervention, including lymphadenectomy for early tumors, remains the primary approach.Conclusion: Cancer at the esophagogastric junction resembles gastric cancer more than esophageal cancer. Surgical intervention, though primary, shows high recurrence rates, emphasizing the need for multimodal approaches like chemotherapy, radiotherapy, and nutritional therapies.
Keywords: esophagogastric junction; esophageal neoplasms; neoplasm; therapeutic actions